PRESENT STATUS AND KEY TO INDIAN FAIRYFLY GENERA (HYMENOPTERA: MYMARIDAE) - ATHITHYA, A.; MANICKAVASAGAM, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Indian mymarid genera is updated. Keys to diagnose all the known 10 generic groups and 39 mymarid genera (generic group wise) of India are furnished in accordance with the recent (2021) changes in classification of mymarids.